Research progress in the treatment of perianal hidradenitis suppurativa - Yun Yu; Wu Yuqi; Kang Jian; Tang Xiao (结直肠肛门外科)
［Abstract］ Perianal hidradenitis suppurativa is a chronic inflammatory skin disease occurring around the anus, characterized by painful, deep-seated inflammatory lesions that subsequently develop into abscesses, sinus tracts, and scarring. The etiology of this disease is primarily associated with genetic, immune, endocrine, and lifestyle factors, although the specific mechanisms remain unclear. Mild cases are typically treated with medication, while severe or recurrent cases should promptly undergo surgical intervention. This article provides a comprehensive review of the etiology, pathogenesis, and current treatment progress of perianal hidradenitis suppurativa.